Exploring the contribution of pro-inflammatory cytokines to impaired wound healing in diabetes - Nirenjen, S.; Narayanan, J.; Tamilanban, T.; Subramaniyan, Vetriselvan; Chitra, V.; Fuloria, Neeraj Kumar; Wong, Ling Shing; Ramachawolran, Gobinath; Sekar, Mahendran; Gupta, Gaurav; Fuloria, Shivkanya; Chinni, Suresh V.; et al. (Frontiers in Immunology, 2023)
Impaired wound healing is the most common and significant complication of Diabetes. While most other complications of Diabetes have better treatment options, diabetic wounds remain a burden as they can cause pain and suffering in patients. Wound closure and repair are orchestrated by a sequence of events aided by the release of pro-inflammatory cytokines, which are dysregulated in cases of Diabetes, making the wound environment unfavorable for healing and delaying the wound healing processes. This concise review provides an overview of the dysregulation of proinflammatory cytokines and offers insights into better therapeutic outcomes.Although many therapeutic approaches have been lined up nowadays to treat Diabetes, there are no proper treatment modalities proposed yet in treating diabetic wounds due to the lack of understanding about the role of inflammatory mediators, especially Pro-inflammatory mediators-Cytokines, in the process of Wound healing which we mainly focus on this review.Although complications of Diabetes mellitus are most reported after years of diagnosis, the most severe critical complication is impaired Wound Healing among Diabetes patients. Even though Trauma, Peripheral Artery Disease, and Peripheral Neuropathy are the leading triggering factors for the development of ulcerations, the most significant issue contributing to the development of complicated cutaneous wounds is wound healing impairment. It may even end up with amputation.Newer therapeutic approaches such as incorporating the additives in the present dressing materials, which include antimicrobial molecules and immunomodulatory cytokines is of better therapeutic value.